High-strength flame-retardant TPU (thermoplastic polyurethane) cable material, preparation method thereof and cable prepared from cable material
By adding modified nano aluminum hydroxide/hexagonal boron nitride nanocomposite powder and composite flame retardant to the TPU cable material, the combustion problem of traditional TPU materials is solved, and the cable material with high strength and excellent flame retardant performance is achieved, which meets the High performance and environmental safety requirements.
Patent Information
- Application Number
- CN202411212211.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-20
AI Technical Summary
Traditional TPU materials are prone to burn when they encounter fire sources, releasing a large amount of heat and harmful gases, which limits their use in situations with high flame retardancy requirements such as mining, subway and ship applications. The existing flame retardant is used in large amounts, making it difficult to Meet environmental protection and safety standards.
High-strength flame retardant TPU cable material, the batching includes TPU, modified nano aluminum hydroxide/hexagonal boron nitride nanocomposite powder, composite flame retardant, anti-hydrolyzer, lubricant and antioxidant, and modified by solution method Nanoaluminum hydroxide/hexagonal boron nitride nanocomposite powder is intensively refined and granulated in a mixer to form a melt blend, and finally granulated through a twin-screw-single screw hot-cut air-cooled granulator unit.
It improves the flame retardant performance and physical and mechanical properties of TPU cable materials, reduces the amount of flame retardant, achieves excellent flame retardant effect and mechanical properties, and meets the needs of high performance and environmental protection and safety.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of electric wires and cables, and in particular to a high-strength flame-retardant TPU cable material, a preparation method and a cable made from the cable material. Background Art
[0002] In the cable industry, TPU has attracted much attention due to its excellent mechanical properties and chemical resistance. Traditional TPU materials are easy to burn when encountering a fire source, and they release a lot of heat and harmful gases when burning, which greatly limits its scope of use in certain occasions that require high flame retardancy, such as mining, subway and ship applications. Therefore, the development of a new type of high-strength flame-retardant TPU material that can not only meet the high-performance requirements of the cable industry, but also meet the new environmental protection and safety standards, reduce the amount of flame retardants while maintaining good physical and mechanical properties, has become the focus of technological innovation. Summary of the invention
[0003] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a high-strength flame-retardant TPU cable material and a preparation method and cable thereof, aiming to solve the problem of insufficient physical and mechanical properties and flame retardant properties of the current TPU cable.
[0004] To achieve the above-mentioned purpose, the present invention proposes a high-strength flame-retardant TPU cable material. The ingredients of the high-strength flame-retardant TPU cable material, measured by weight, include: 90-100 parts of TPU; 4-12 parts of modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powder; 10-20 parts of composite flame retardant; 0.5-2 parts of anti-hydrolysis agent; 0.5-1 parts of lubricant; and 0.4-1 parts of antioxidant.
[0005] Optionally, the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder is 8-10 parts.
[0006] Optionally, the TPU includes at least one of the polyether TPU elastomers 8570A, 8575, 8580, 8585, 8588, 8590A, 8595, 8555D, 8565D, 85180 and 85190.
[0007] Optionally, the composite flame retardant is a compound of a phosphorus-based flame retardant and a nitrogen-based flame retardant, and the weight ratio of the phosphorus-based flame retardant to the nitrogen-based flame retardant is (1-3): (1-3).
[0008] Optionally, the anti-hydrolysis agent is at least one of a monomeric carbodiimide anti-hydrolysis agent and a polymeric carbodiimide anti-hydrolysis agent.
[0009] Optionally, the lubricant is at least one of fatty acids, fatty amides, metal soaps and fatty alcohols.
[0010] Optionally, the antioxidant is at least one of a hindered phenol antioxidant, a hindered amine antioxidant, a phosphate antioxidant and a thioester antioxidant.
[0011] In order to achieve the above-mentioned purpose, the present invention also proposes a method for preparing a high-strength flame-retardant TPU cable material, comprising the following steps: preparing modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder: preparing modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder by a solution method from hexagonal boron nitride, isopropanol, aluminum chlorohydrate, n-butanol, ammonia water, and a silane coupling agent; preparing high-strength flame-retardant TPU cable material: pre-mixing TPU, modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, composite flame retardant, anti-hydrolysis agent, lubricant and antioxidant, and then mixing them in an internal mixer to prepare a molten blend, granulating the molten blend in a twin-screw-single-screw hot-cut air-cooled granulation unit, and then performing secondary air cooling and vibration screening to finally obtain a high-strength flame-retardant TPU cable material.
[0012] Optionally, the preparation method of the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder comprises the following steps: exfoliating hexagonal boron nitride to form hexagonal boron nitride nano sheets and hydroxylating the sheets to obtain micro-nano hexagonal boron nitride powder, then in situ growing nano aluminum hydroxide on the surface of the micro-nano hexagonal boron nitride powder to obtain nano aluminum hydroxide / hexagonal boron nitride nano composite powder, then adding the nano aluminum hydroxide / hexagonal boron nitride nano composite powder and a silane coupling agent to an ethanol solution, and drying after ultrasonic dispersion and vacuum filtration to obtain a modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder.
[0013] Optionally, the silane coupling agent is at least one of 3-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.
[0014] In order to achieve the above object, the present invention also provides a cable, which is made of any one of the above high-strength flame-retardant TPU cable materials.
[0015] Beneficial effects of the present invention: In the present invention, poly TPU, modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, composite flame retardant and anti-hydrolysis agent are mixed together as a mixed elastomer component of high-strength flame-retardant TPU cable material. Since hexagonal boron nitride has excellent thermal conductivity and thermal stability, it can improve the heat resistance of nano aluminum hydroxide. Therefore, the combination of the two has the characteristics of synergistic flame retardancy and smoke suppression. The use of composite flame retardant can reduce its dosage and achieve excellent flame retardant effect. By adding modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, the flame retardant effect of high-strength flame retardant TPU cable material can be improved to a certain extent, and the physical and mechanical properties of the matrix can be improved, and the material's ability to resist deformation is improved, thereby realizing the composite modification of TPU cable material, so that it obtains excellent physical and mechanical properties and flame retardancy. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0017] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.
[0018] In order to facilitate the understanding of this embodiment, the symbols, instruments and terms are explained below: TPU: Thermoplastic Polyurethanes, is a material widely used in various fields. It has excellent physical properties such as high strength, high toughness, wear resistance, oil resistance, etc., so it is used to manufacture various products, including but not limited to daily necessities, sporting goods, toys, decorative materials, etc.
[0019] In the cable industry, TPU has attracted much attention due to its excellent mechanical properties and chemical resistance. Traditional TPU materials are easy to burn when encountering a fire source, and they release a lot of heat and harmful gases when burning, which greatly limits its scope of use in certain occasions that require high flame retardancy, such as mining, subway and ship applications. Therefore, the development of a new type of high-strength flame-retardant TPU material that can not only meet the high-performance requirements of the cable industry, but also meet the new environmental protection and safety standards, reduce the amount of flame retardants while maintaining good physical and mechanical properties, has become the focus of technological innovation.
[0020] To solve the above problems, the present invention proposes a high-strength flame-retardant TPU cable material. The ingredients of the high-strength flame-retardant TPU cable material, measured in parts by weight, include: 90-100 parts of TPU; 4-12 parts of modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powder; 10-20 parts of composite flame retardant; 0.5-2 parts of anti-hydrolysis agent; 0.5-1 parts of lubricant; and 0.4-1 parts of antioxidant.
[0021] In the present invention, TPU, modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, composite flame retardant and anti-hydrolysis agent are mixed together as a mixed elastomer component of high-strength flame-retardant TPU cable material. Since hexagonal boron nitride has excellent thermal conductivity and thermal stability, it can improve the heat resistance of nano aluminum hydroxide. Therefore, the combination of the two has the characteristics of synergistic flame retardancy and smoke suppression. The use of composite flame retardant can reduce its dosage and achieve excellent flame retardant effect. By adding modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, the flame retardant effect of high-strength flame retardant TPU cable material can be improved to a certain extent, and the physical and mechanical properties of the matrix can be improved, and the material's ability to resist deformation is improved, thereby realizing the composite modification of TPU cable material, so that it obtains excellent physical and mechanical properties and flame retardancy.
[0022] In some embodiments, the ingredients of the high-strength flame-retardant TPU cable material, measured in parts by weight, preferably include: 90-100 parts of TPU; 4-12 parts of modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powder; 10-20 parts of composite flame retardant; 0.5-2 parts of anti-hydrolysis agent; 0.5-1 parts of lubricant; and 0.4-1 parts of antioxidant.
[0023] Furthermore, 8-10 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder.
[0024] In some embodiments, the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder is preferably 8 parts.
[0025] In some embodiments, the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder is preferably 10 parts.
[0026] Further, the TPU includes at least one of the polyether TPU elastomers 8570A, 8575, 8580, 8585, 8588, 8590A, 8595, 8555D, 8565D, 85180 and 85190, and the proportion thereof is 90-100 parts.
[0027] In some embodiments, the TPU is polyether TPU elastomer 8570A, and its weight fraction is 100 parts.
[0028] Furthermore, the composite flame retardant is a compound of a phosphorus-based flame retardant and a nitrogen-based flame retardant, and the weight ratio of the phosphorus-based flame retardant to the nitrogen-based flame retardant is (1-3): (1-3).
[0029] Composite flame retardants are compounded from phosphorus-based flame retardants and nitrogen-based flame retardants. They utilize multiple flame retardant components to work together to form a more effective flame retardant, thereby making up for the shortcomings of a single organic flame retardant element, thereby better balancing the relationship between flame retardant dosage, performance and cost, and being more environmentally friendly and safe.
[0030] In some embodiments, the composite flame retardant is a compound of a phosphorus-based flame retardant red phosphorus and a nitrogen-based flame retardant melamine.
[0031] In some embodiments, the weight ratio of the phosphorus-based flame retardant to the nitrogen-based flame retardant is 1:1.
[0032] In some embodiments, the composite flame retardant is a compound of a phosphorus-based flame retardant phosphonate and a nitrogen-based flame retardant dicyandiamide. In some embodiments, the weight ratio of the phosphorus-based flame retardant to the nitrogen-based flame retardant is 1:3.
[0033] Furthermore, the anti-hydrolysis agent is at least one of a monomeric carbodiimide anti-hydrolysis agent and a polymeric carbodiimide anti-hydrolysis agent.
[0034] Anti-hydrolysis agents can react with the terminal carboxyl groups, terminal amine groups and terminal hydroxyl groups generated during the hydrolysis of polymers to generate stable harmless products, effectively preventing further degradation and chain breaking, effectively inhibiting the hydrolysis of materials, and stabilizing their initial mechanical properties. At the same time, they can also seal the active terminal carboxyl groups of the materials, repair damaged polyester and polyurethane materials, and extend the service life of polymer products under harsh working conditions such as high temperature and humidity.
[0035] In some embodiments, the anti-hydrolysis agent is a monomeric carbodiimide anti-hydrolysis agent acetone.
[0036] In some embodiments, the anti-hydrolysis agent is the monomeric carbodiimide anti-hydrolysis agent chlorobenzene.
[0037] In some embodiments, the anti-hydrolysis agent is a compound of a monomeric carbodiimide anti-hydrolysis agent dichloromethane and a polymeric carbodiimide anti-hydrolysis agent.
[0038] Furthermore, the lubricant is at least one of fatty acids, fatty amides, metal soaps, and fatty alcohols.
[0039] Lubricants can improve fluidity during processing, increase the impact strength of materials, reduce water absorption on the cable surface, improve cable scratches and surface defects, and reduce heat release rate and smoke generation, all of which help improve cable performance and safety.
[0040] Furthermore, the antioxidant is at least one of a hindered phenol antioxidant, a hindered amine antioxidant, a phosphate antioxidant and a thioester antioxidant.
[0041] Adding antioxidants can prevent the thermo-oxidative degradation of elastomers and significantly improve the electrical and mechanical properties of the material.
[0042] In some embodiments, the lubricant is preferably 0.5 parts of a fatty acid-based lubricant.
[0043] In some embodiments, the antioxidant is preferably 0.5 parts of bis(octadecyl)hydroxylamine.
[0044] In order to solve the above problems, the present invention also proposes a method for preparing a high-strength flame-retardant TPU cable material, comprising the following steps: S1: preparing modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder: preparing modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder by a solution method using hexagonal boron nitride, isopropanol, aluminum chlorohydrate, n-butanol, ammonia water, and a silane coupling agent; In this scheme, the hexagonal boron nitride in the modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powder is treated to obtain a micro-nano hexagonal boron nitride, which has the characteristics of both nanomaterials and micron fillers. First, the micron sheet filler can improve the scratch resistance of the matrix due to the low friction coefficient of hexagonal boron nitride itself; secondly, the structure of the nanosheet makes the subsequent growth of nano-aluminum hydroxide, and the specific surface area of the nano-aluminum hydroxide generated in situ on the surface of the hexagonal boron nitride nanosheet is large, which reduces the partial pressure of water vapor on the particle surface, and can improve the flame retardant effect to a certain extent. In addition, due to the excellent thermal conductivity and thermal stability of hexagonal boron nitride, it can improve the heat resistance of nano-aluminum hydroxide, so the combination of the two has the characteristics of synergistic flame retardancy and smoke suppression, and the use of flame retardants in combination can reduce its dosage and achieve excellent flame retardant effects. Finally, the sheet structure of micro-nano hexagonal boron nitride can also change the path of oxygen, moisture, etc. entering the resin matrix, thereby improving the aging resistance.
[0045] S2: preparing high-strength flame-retardant TPU cable material: pre-mixing TPU, modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, composite flame retardant, anti-hydrolysis agent, lubricant and antioxidant, and then mixing them in an internal mixer to prepare a molten blend; In some embodiments, internal mixing is performed in an internal mixer.
[0046] S3: The molten blend is granulated by extrusion, followed by air cooling and screening to finally obtain a high-strength flame-retardant TPU cable material.
[0047] In some embodiments, extrusion granulation is achieved by a twin-screw-single-screw hot-cut air-cooled granulation unit.
[0048] Furthermore, the preparation method of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder comprises the following steps: Hexagonal boron nitride is exfoliated to form hexagonal boron nitride nanosheets, which are then hydroxylated to obtain micro-nano hexagonal boron nitride powders. Nano-aluminum hydroxide is then in-situ grown on the surface of the micro-nano hexagonal boron nitride powders to obtain nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders. Subsequently, the nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders and a silane coupling agent are added to an ethanol solution, and the solution is subjected to ultrasonic dispersion and vacuum filtration and then dried to obtain modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders.
[0049] In some embodiments, hexagonal boron nitride is placed in an isopropanol solution, and then ultrasonicated for 24 hours using an ultrasonic disperser at a power of 500 W. After vacuum filtration, the solution is dried in a vacuum oven at 80-100° C. for 6-8 hours to obtain micro-nano hexagonal boron nitride powder.
[0050] In some embodiments, aluminum chlorohydrate is dissolved in n-butanol solution, and then hexagonal boron nitride nanosheet powder is placed in the solution and stirred evenly, and then ammonia water is quickly poured into the n-butanol solution of aluminum chlorohydrate under vigorous stirring to react for 1-2 hours. After the reaction is completed, vacuum filtration is performed and deionized water is used to wash 5-8 times until the Cl - .
[0051] In some embodiments, nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder and a silane coupling agent are added to an ethanol solution, ultrasonically dispersed at 40-80°C with a power of 120W for 4 hours, followed by vacuum filtration and drying in a vacuum oven at 70-90°C for 24-30 hours to obtain a modified nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder.
[0052] Furthermore, the silane coupling agent is at least one of 3-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane, and γ-glycidyloxypropyltrimethoxysilane.
[0053] In some embodiments, the silane coupling agent is preferably 3-aminopropyltriethoxysilane.
[0054] In order to solve the above problems, the present invention also provides a cable, which is made by the above-mentioned preparation method of the high-strength flame-retardant TPU cable material.
[0055] The content of the present invention is explained below through specific examples and data.
[0056] Embodiment 1: The hexagonal boron nitride is peeled off to form hexagonal boron nitride nanosheets and hydroxylated. The hexagonal boron nitride is placed in an isopropanol solution, and then ultrasonically dispersed at 500w for 24 hours, vacuum filtered and dried in a vacuum oven at 80-100℃ for 6-8 hours to obtain micro-nano hexagonal boron nitride powder. Secondly, nano aluminum hydroxide is grown in situ on the surface of hexagonal boron nitride nanosheets. Aluminum chlorohydrate is dissolved in n-butanol solution, and the hexagonal boron nitride nanosheet powder is placed in the solution and stirred evenly, and then ammonia water is quickly poured into the n-butanol solution of aluminum chlorohydrate under vigorous stirring to react for 1-2 hours. After the reaction is completed, vacuum filter again and wash with deionized water 5-8 times to clean Cl - Then, the nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder and the silane coupling agent were added to the ethanol solution, and ultrasonicated at 40-80° C. with a power of 120 W for 4 h using an ultrasonic disperser, followed by vacuum filtration and drying in a vacuum oven at 70-90° C. for 24-30 h, and finally the modified nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder was obtained.
[0057] 100 parts of TPU, 4 parts of nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 15 parts of composite flame retardant, 1 part of anti-hydrolysis agent, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed and then extruded and granulated to obtain high-strength flame-retardant TPU cable material.
[0058] Embodiment 2: The preparation method is the same as that of Example 1, except that: 100 parts of TPU, 6 parts of nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 15 parts of composite flame retardant, 1 part of anti-hydrolysis agent, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed and then extruded and granulated to obtain high-strength flame-retardant TPU cable material.
[0059] Embodiment 3: The preparation method is the same as that of Example 1, except that: 100 parts of TPU, 8 parts of nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 15 parts of composite flame retardant, 1 part of anti-hydrolysis agent, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed and then extruded and granulated to obtain high-strength flame-retardant TPU cable material.
[0060] Embodiment 4: The preparation method is the same as that of Example 1, except that: 100 parts of TPU, 10 parts of nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 15 parts of composite flame retardant, 1 part of anti-hydrolysis agent, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed and then extruded and granulated to obtain high-strength flame-retardant TPU cable material.
[0061] Embodiment 5: The preparation method is the same as that of Example 1, except that: 100 parts of TPU, 12 parts of nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 15 parts of composite flame retardant, 1 part of anti-hydrolysis agent, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed and then extruded and granulated to obtain high-strength flame-retardant TPU cable material.
[0062] Embodiment 6: The preparation method is the same as that of Example 1, except that: 100 parts of TPU, 8 parts of nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 10 parts of composite flame retardant, 1 part of anti-hydrolysis agent, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed and then extruded and granulated to obtain high-strength flame-retardant TPU cable material.
[0063] Comparative Example 1: 100 parts of TPU, 15 parts of composite flame retardant, 1 part of anti-hydrolysis agent, 0.5 parts of lubricant and 0.5 parts of antioxidant were mixed and then extruded and granulated to obtain high-strength flame-retardant TPU cable material.
[0064] Comparative Example 2: 100 parts of TPU, 8 parts of hexagonal boron nitride, 15 parts of composite flame retardant, 1 part of anti-hydrolysis agent, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed and then extruded and granulated to obtain high-strength flame-retardant TPU cable material.
[0065] Comparative Example 3: The preparation method is the same as that of Example 1, except that: 100 parts of TPU, 8 parts of nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 1 part of anti-hydrolysis agent, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed and then extruded and granulated to obtain a high-strength flame-retardant TPU cable material.
[0066] Comparative Example 4: The preparation method is the same as that of Example 1, except that: 100 parts of TPU, 1 part of nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder, 15 parts of composite flame retardant, 1 part of anti-hydrolysis agent, 0.5 part of lubricant and 0.5 part of antioxidant are mixed and then extruded and granulated to obtain high-strength flame-retardant TPU cable material.
[0067] Comparative Example 5: The preparation method is the same as that of Example 1, except that: 100 parts of TPU, 15 parts of nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 15 parts of composite flame retardant, 1 part of anti-hydrolysis agent, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed and then extruded and granulated to obtain high-strength flame-retardant TPU cable material.
[0068] The components and important preparation variables of Examples 1-6 and Comparative Examples 1-5 are summarized in Table 1.
[0069] Table 1. Components of Examples 1-6 and Comparative Examples 1-5 of the present invention
[0070] According to relevant test standards, the high-strength flame-retardant TPU cable materials in the above Examples 1-6 and Comparative Examples 1-5 were tested for tensile strength, elongation at break, flame retardancy, and scratch resistance, and the test results were recorded in the following Table 2: Table 2. Performance of Examples 1-6 and Comparative Examples 1-5 of the present invention
[0071] According to the above test results, it can be seen that in Examples 1-5, the added amount of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder gradually increases within the range of 4-12 parts by weight of the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder in the present invention. The added amounts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder in Examples 1-5 are 4 parts, 6 parts, 8 parts, 10 parts and 12 parts, respectively. According to the test results, as the amount of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder increases, the TPU cable prepared in Examples 1-5 increases. The tensile strength of the material also increases, the elongation at break gradually decreases, and the tear strength gradually increases while maintaining excellent flame retardant properties. Therefore, adding modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder can improve the strength of TPU and improve the flame retardant properties of the material; 12 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder and 15 parts of composite flame retardant are added in Example 5, and 8 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder and 10 parts of composite flame retardant are added in Example 6. The tensile strength of Example 5 is 37.2 MPa, elongation at break is 522%, tear strength is 79.8 kN / m, and flame retardant grade is V-0. The tensile strength of Example 6 is 37.7 MPa, elongation at break is 555%, tear strength is 78 kN / m, and flame retardant grade is V-0. It can be seen from the test results of Examples 5 and 6 that when the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder is used in combination with commonly used flame retardants on the market, the flame retardant efficiency can be improved, the amount of flame retardant used can be reduced, and excellent flame retardant effect can be achieved.In Comparative Examples 1-3, the effects of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, hexagonal boron nitride and composite flame retardant were tested. The test results showed that the use of composite flame retardant alone in Comparative Example 1 could not achieve the ideal flame retardant effect, and its mechanical properties were also poor. In Comparative Example 2, untreated hexagonal boron nitride and composite flame retardant were used in combination. The test results showed that the performance of the TPU material obtained in Comparative Example 2 was the worst among all formulations. In Comparative Example 3, only modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder was used, and no composite flame retardant was used. It can be concluded that the mechanical properties of Comparative Example 3 are good, but the flame retardant properties are not good. Therefore, the mechanical properties and flame retardant ability of TPU cable materials can be improved by cooperating with modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder and composite flame retardant; in Comparative Examples 4-5, modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder not in the present invention is added in the range of 4-12 parts by weight. Aluminum hydroxide / hexagonal boron nitride nano-composite powder, test results show that the tensile strength, tear strength and flame retardant grade of Example 4 are all lower than those of Example 5, and the elongation at break of Example 5 is 265%. Due to the addition of a large amount of modified nano aluminum hydroxide / hexagonal boron nitride nano-composite powder, relative to the matrix, the more the modified nano aluminum hydroxide / hexagonal boron nitride nano-composite powder, the greater the probability of powder agglomeration, and nano-agglomeration will affect the elongation at break of the material. Therefore, the formula of Example 5 cannot achieve the improvement of the mechanical properties of the TPU cable material. Therefore, the flaky structure of the modified nano aluminum hydroxide / hexagonal boron nitride nano-composite powder can change the path of oxygen, moisture, etc. entering the resin matrix, thereby improving the physical and mechanical properties. While improving the flame retardant properties of the material, it also ensures the strength of the TPU material and reduces the cost to a certain extent. The high flame retardant and high strength characteristics of the high-flame retardant and high-strength TPU material proposed in the present invention can meet the high performance requirements of the cable industry.
[0072] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A high-strength flame-retardant TPU cable material, It is characterized in that The ingredients of the high-strength flame-retardant TPU cable material include, by weight: TPU 90-100 parts; 4-12 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder; 10-20 parts of composite flame retardant; Anti-hydrolysis agent 0.5-2 parts; Lubricant 0.5-1 part; Antioxidant 0.4-1 part.
2. The high-strength flame-retardant TPU cable material according to claim 1, It is characterized in that The modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder is 8-10 parts.
3. The high-strength flame-retardant TPU cable material according to claim 1, It is characterized in that The TPU includes at least one of the polyether TPU elastomers 8570A, 8575, 8580, 8585, 8588, 8590A, 8595, 8555D, 8565D, 85180 and 85190.
4. The high-strength flame-retardant TPU cable material according to claim 1, It is characterized in that The composite flame retardant is compounded by a phosphorus-based flame retardant and a nitrogen-based flame retardant, and the weight ratio of the phosphorus-based flame retardant to the nitrogen-based flame retardant is (1-3): (1-3).
5. The high-strength flame-retardant TPU cable material according to claim 1, It is characterized in that The anti-hydrolysis agent is at least one of a monomeric carbodiimide anti-hydrolysis agent and a polymeric carbodiimide anti-hydrolysis agent.
6. The high-strength flame-retardant TPU cable material according to claim 1, It is characterized in that The lubricant is at least one of fatty acids, fatty amides, metal soaps and fatty alcohols.
7. The high-strength flame-retardant TPU cable material according to claim 1, It is characterized in that The antioxidant is at least one of a hindered phenol antioxidant, a hindered amine antioxidant, a phosphate antioxidant and a thioester antioxidant.
8. A method for preparing high-strength flame-retardant TPU cable material, It is characterized in that The following steps are involved: Preparation of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder: preparing modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder by a solution method using hexagonal boron nitride, isopropyl alcohol, aluminum chlorohydrate, n-butanol, ammonia water, and a silane coupling agent; Preparation of high-strength flame-retardant TPU cable material: TPU, modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powder, composite flame retardant, anti-hydrolysis agent, lubricant and antioxidant are pre-mixed evenly, and then mixed in an internal mixer to prepare a molten blend, and the molten blend is granulated in a twin-screw-single-screw hot-cut air-cooled granulation unit, followed by secondary air cooling and vibration screening to finally obtain a high-strength flame-retardant TPU cable material.
9. The method for preparing the high-strength flame-retardant TPU cable material according to claim 7, It is characterized in that The method for preparing the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder comprises the following steps: Hexagonal boron nitride is exfoliated to form hexagonal boron nitride nanosheets, which are then hydroxylated to obtain micro-nano hexagonal boron nitride powders. Nano-aluminum hydroxide is then in-situ grown on the surface of the micro-nano hexagonal boron nitride powders to obtain nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders. Subsequently, the nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders and a silane coupling agent are added to an ethanol solution, and the solution is subjected to ultrasonic dispersion and vacuum filtration and then dried to obtain modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders.
10. The method for preparing the high-strength flame-retardant TPU cable material according to claim 8, It is characterized in that The silane coupling agent is at least one of 3-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.
11. A cable, It is characterized in that The cable is made from the cable material according to claim 1.
Citation Information
Patent Citations
Preparation method of nanometer calcium hydroxide / hexagonal boron nitride nano-composite
CN107140669A
Magnesium hydroxide / hexagonal boron nitride nanocomposite material and preparation method thereof
CN107353433A
Nano barium hydroxide / hexagonal boron nitride nano composite material and preparation method thereof
CN107880903A
Preparation method of modified hexagonal boron nitride flame retardant and water-based intumescent fire-retardant coating
CN110343291A
Flame-retardant matte thermoplastic polyurethane elastomer cable material and preparation method thereof
CN118344725A
